Differences in Auditors' Materiality Assessments When Auditing Financial Statements and Sustainability Reports - Moroney, Robyn; Trotman, Ken T. (Contemporary Accounting Research, 2016)
Abstract With increased interest in voluntary sustainability reports from investors and other stakeholders, more companies are having these reports assured. The issue of what is considered material in these assurance engagements is important, and yet research on materiality has focused only on financial statement audits. This article reports the results of an experiment where auditors assess the materiality of audit differences in the same magnitude for both a financial audit and a sustainability (water) assurance engagement. Two factors, the risk of breaching a contract and community impact, are manipulated between‐subjects. We find that auditors assess the materiality of an audit difference significantly higher for a financial case than for a water case. This difference is significantly greater when there is no risk of breaching a contract than when there is a risk of breaching a contract. The risk of breaching a contract has a stronger effect on the difference in auditors' materiality assessments when there is no community impact than when there is a community impact. Overall our findings suggest that qualitative factors have a greater impact on sustainability (water) materiality assessments than on financial statement materiality assessments when an audit difference is between 5 percent and 10 percent of a relevant base. Understanding the factors that impact material judgments in sustainability reports is important as these factors affect the reliability of the reported disclosures.